Pulse and pulsating supercharging phenomena in a semi-enclosed pipe - Fei Wang; Heng Li (Scientific Reports, 2023)
Abstract Considering the discontinuous square pulse wave and continuous sine pulsating wave, we report a distinctive supercharging phenomenon of fluid in a water-filled semi-enclosed pipe and reveal the supercharging regularity. We demonstrate that there can be significant supercharging phenomena at the pipe end-face if the water is periodically injected at the pipe inlet with certain frequency. Compared to the traditional pulsating injection method, the present injection strategy can remarkably enhance the peak pressure of the water at the end face of the pipe. We explained this phenomenon by numerical simulations based on the computational fluid dynamic method. It’s found that there is a quantitative relationship between the optimal pulse frequency, pipe length and wave speed. The proposed frequency model is suitable for the multi-waveform, such as sine wave, square wave and arcuate wave. The fluid pressure at the pipe end-face intermittently increases and the end-face peak pressure is largest when the inlet injection frequency equals to the optimal frequency.